Estrogen Effects on the Mammary Gland in Early and Late Life and Breast Cancer Risk - Dall, Genevieve Victoria; Britt, Kara Louise (Frontiers in Oncology, 2017)
A woman has an increased risk of breast cancer if her lifelong estrogen exposure is increased due to an early menarche, a late menopause and/or an absence of childbearing. For decades it was presumed that the number of years of exposure drove the increased risk, however recent epidemiological data has shown that early life exposure (young menarche) has a more significant effect on cancer risk that late menopause. Thus rather than the overall exposure it seems that the timing of hormone exposure plays a major role in defining breast cancer risk. In support of this it is also known that aberrant hormonal exposure prior to puberty can also increase breast cancer risk, yet the elevated estrogen levels during pregnancy decrease breast cancer risk. This suggests that the effects of estrogen on the mammary gland/breast are age-dependent. In this review article we will discuss the existing epidemiological data linking hormone exposure and estrogen receptor positive breast cancer risk including menarche, menopause, parity and aberrant environmental hormone exposure. We will discuss the predominantly rodent generated experimental data that confirm the association with hormone exposure and breast cancer risk, confirming its use as a model system. We will review the work that has been done attempting to define the direct effects of estrogen on the breast, which are beginning to reveal the mechanism of increased cancer risk. We will then conclude with our views on the most pertinent questions to be addressed experimentally in order explore the relationship between age, estrogen exposure and breast cancer risk.